Maternal Obesity - A Risk Factor For Metabolic Syndrome In Children - Morea, Melinda; Miu, Nicolae; Morea, Vicenţiu Florin; Cornean, Rodica (Medicine and Pharmacy Reports, 2014)
Objective. To determine the association between the metabolic syndrome in children (MS) and the pre-pregnancy nutritional status of the mother. Design and methods. A total number of 180 children aged between 6-19 years were examined. Self reported data about parents and their children were collected. The children underwent physical examination; weight, height, waist circumference, blood pressure (BP) were measured. The nutritional status of the children was assessed by body mass index (BMI) and laboratory tests needed to diagnose MS were performed. IDF criteria for MS were used in children 10 years and older, and age and gender specific cut-off points in children younger than 10 years. The mothers were classified in the normal weight, overweight and obese categories accordig to the pre-pregnancy BMI. The statistical analysis of the data was descriptive and inferential analysis. In the bivariate analysis of the association between qualitative variables, we used the Chi-Square test and the exact Fisher test. The statistical analysis was performed with SPSS v 13.0. Results. 73 (40.55%) children were normal weight, 54 (30%) were overweight and 53 (29.44%) were obese. None of the normal weight children, 16 (29.60%) of the overweight and 23 (43.40%) of the obese ones had MS; 125 (69.44%) of the mothers were normal weight, 44 (24.44%) were overweight and 11 (6.11%) were obese. Pre-pregnancy maternal BMI was significantly associated with offspring MS in both genders, obese children and in the 10-16 age group. Conclusions. Pre-pregnancy maternal overweight/obesity represents a risk factor for offspring MS. The results are very difficult to compare between studies because of different cut off values and definition of MS in children. If prevention is the goal rather than treatment, the perinatal period may be an important focus for future research.